The Effect of a Preconception Nutrition Supplement on One Carbon Metabolites (P24-028-19). (13th June 2019) - Gilley, Stephanie; Sticca, Evan; Kerns, Mattie; Palacios, Alexandra; Jambal, Purevsuren; Kemp, Jennifer; Westcott, Jamie; Garces, Ana; Figueroa, Lester; Hendricks, Audrey; Hambidge, Michael; Krebs, Nancy; et al.
Abstract: Objectives: Studies in both animals and humans have shown that maternal dietary restriction and supplementation of one carbon (1C) metabolites (methyl donors), such as methionine and choline, can impact offspring growth, insulin resistance, and DNA methylation. However, there has been limited longitudinal research of 1C metabolite concentrations over the reproduction cycle of human pregnancy. The purpose of this study was to investigate if 1C metabolite concentrations change prior to and during pregnancy and if a preconception lipid-based nutrition supplement (LNS) influences such changes. Methods: This study was a secondary analysis as part of the Women First study (clinicaltrials.gov, NCT01883193), a large, randomized controlled trial investigating whether the timing of maternal LNS initiation would impact fetal growth and development. The study arms were supplementation at least 3 months prior to conception (Arm 1), supplementation at ∼12 weeks of gestation (Arm 2), or no supplementation (Arm 3). Dried blood spot (DBS) cards were collected at study enrollment prior to conception, and at 12 and 34 weeks gestation. A targeted 1C metabolite assay (27 metabolites) was performed on a subset of DBS samples from Guatemalan women ( n = 134) at each time point using liquid chromatography/tandem mass spectrometry. Longitudinal analyses were performed using linear mixed modeling to investigate the influence of time and LNS on these metabolites. Results: The concentrations of two metabolites were changed by intervention status: asymmetric dimethylarginine (ADMA) and symmetric dimethylarginine (SDMA). Twenty-one of 27 metabolites significantly changed from preconception and across gestation after correcting for multiple testing using the Bonferroni correction ( P < 0.00185). Conclusions: Preconception LNS significantly decreased the level of ADMA, a metabolite which has been implicated in intrauterine growth restriction and preeclampsia. More work is needed to determine whether this intervention could influence development of these conditions. Funding Sources: Bill & Melinda Gates Foundation, National Institutes of Health.